Preclinical evaluation of 2-amino-2-[11C]methyl-butanoic acid as a potential tumor-imaging agent in a mouse model. Issue 11 (November 2015) - Suzuki, Chie; Tsuji, Atsushi B.; Kato, Koichi; Sudo, Hitomi; Zhang, Ming-Rong; Saga, Tsuneo
<x xml:space="preserve">Abstract</x> Objective 14C-labeled 2-amino-2-methyl-butanoic acid (Iva) was previously reported to provide high tumor uptake; however, the pharmacokinetic properties of 11C-labeled Iva have not been characterized. In the present study, we evaluated the potential of [11C]Iva as a PET probe for tumor imaging. Methods [11C]Iva was incubated in mouse serum for 60 min at 37°C and then analyzed by high-performance liquid chromatography and thin-layer chromatography. In-vitro cellular uptake of [11C]Iva was determined in PBS and sodium-free buffer at 37°C using SY human small-cell lung cancer cells. The effects of inhibitors of amino acid transporters on [11C]Iva uptake were also determined in PBS. In-vivo distribution and dynamic PET studies were conducted in SY tumor-bearing mice. Results [11C]Iva was stable in mouse serum in vitro for 60 min. The cellular uptake of [11C]Iva was linearly increased for 20 min in both PBS and sodium-free buffer and almost completely inhibited by an inhibitor of system L amino acid transporters and another of LAT1, a transporter of system L. In-vivo distribution and dynamic PET studies showed that [11C]Iva was highly accumulated in tumor, but not in normal tissues, except for the pancreas and kidneys. The [11C]Iva uptake ratio of tumor to several normal tissues, such as the lung, muscle, and brain, was high. Conclusion [11C]Iva was stable in mouse serum and transported through system L amino acid transporters including LAT1, which is highly expressed in several tumors. [11C]Iva is a promising PET probe for noninvasive tumor imaging.